APLIKASI SISTEM FUEL CELL SEBAGAI ENERGI RAMAH LINGKUNGAN DI SEKTOR TRANSPORTASI DAN PEMBANGKIT - Hasan, Achmad (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Fuel cell is a device which is purposed to convert chemical energy into electric energy and produce water as side result. Fuel cell technology doesn’t produce emission and doesn’t make noises and also as environmental friendly energy has a high efficiency until 45% in fuel conversion to electricity, and it can be higher until 60% – 80% if it isco-generation. A fuel processing system converts hydrocarbon or other organic fuels to hydrogen of composition and purity suitable for fuel cell operation. The fuels include petroleum derived liquids, such as naphtha and gasoline, petroleum derived gases, such as methane and propane, and other fuel such as methanol and ethanol. The electrolyte in the center allows only the protons to pass through the membrane to the cathode side of the fuel cell. The electrons cannot pass through this membrane and flow through an external circuit in the form of electric current. As oxygen flows into the fuel cell cathode, another catalyst helps the oxygen, protons, and electrons combine to produce pure water and heat.